MENEMUKAN LOKALITAS BIOLOGICAL ASSETS: PELIBATAN ETNOGRAFIS PETANI APEL - Novan Rizaldy (Universitas Brawijaya, 2012)
Abstract: Finding the locality of Biological Assets: The Involvement of Ethnography of Apple Farmers.The research wants to find the concept of biological assets from apple grower’s view.The research uses ethnography method and is taken in Sumbergondo village, Batu-Malang, East Java. The results are, first, the growers believe that assets or ke’kean are gifts from God that have to be taken care as it’s responsibility. Second, biological assets cannot be separated from their ecological aspect. In this way, soil that is previously detached from biological assetshas to be included in its components.Third, selametan or ceremonial feastis a long-term obligation as a culture reflection to preserve and increase assets forthe future.Abstrak: Menemukan Lokalitas Biological Assets: Pelibatan Etnografis Petani Apel. Penelitian ini bertujuan untuk menemukan konsep biological assets menurut pandangan petani apel. Penelitian ini menggunakan metode etnografi yang dilakukan di desa Sumbergondo, Batu-Malang, Jawa Timur. Hasil penelitian terdiri atas empat hal. Pertama, aset menurut petani adalah ke’kean (pemberian) dari Yang Maha Kuasa yang harus dijaga dan dirawat sebagai sebuah bentuk pertanggungjawaban kepada Tuhan. Kedua, aset biologis tidak bisa terlepas dari aspek ekologinya, sehingga tanah yang sebelumnya terpisah dari aset biologis harus dimasukkan ke dalam komponen asetbiologis. Ketiga, selametan merupakan kewajiban jangka panjang sebagai refleksi kebudayaan untuk memelihara dan meningkatkan aset di masa depan.